2003
DOI: 10.1023/a:1022968303118
|View full text |Cite
|
Sign up to set email alerts
|

Sulfotransferase 1A1 (SULT1A1) Polymorphism, PAH-DNA Adduct Levels in Breast Tissue and Breast Cancer Risk in a Case-Control Study

Abstract: Gene-environment interactions are hypothesized to be major contributors to susceptibility to environmental carcinogens and interindividual variability in cancer risk. We present findings on associations between genetic susceptibility due to inherited polymorphisms of the Phase II detoxification enzyme sulfotransferase 1A1 (SULT1A1), breast cancer risk, and polycyclic aromatic hydrocarbon (PAH)-DNA adducts. A hospital based case-control study was conducted at the New York-Presbyterian Medical Center (NYPMC). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 19 publications
0
32
4
Order By: Relevance
“…The latter association was not observed in women with the His/His genotype. A second study also found a direct association between breast cancer and the His/His genotype that was of borderline significance (44). In the present study, we failed to find any association between SULT1A1 and breast cancer, overall or in subgroups defined by doneness level or smoking.…”
Section: Discussioncontrasting
confidence: 87%
“…The latter association was not observed in women with the His/His genotype. A second study also found a direct association between breast cancer and the His/His genotype that was of borderline significance (44). In the present study, we failed to find any association between SULT1A1 and breast cancer, overall or in subgroups defined by doneness level or smoking.…”
Section: Discussioncontrasting
confidence: 87%
“…Ever smokers with the G/G genotype of the SULT1A1 gene have a significantly higher BC risk of 3.5. Our findings, however, differ from previous reports, which have observed an increased cancer risk or null results associated with the A allele of SULT1A1 [13,15,17]. Positive association was also reported for the A allele of SULT1A1 in esophageal cancer (OR = 3.5; 95% CI = 2.12 -5.87) [18].…”
Section: Discussioncontrasting
confidence: 99%
“…The common polymorphism of SULT1A1 involves a single nucleotide G to A transition at nucleotide 638 (codon 213) in exon 7, which results in an arginine (Arg) to histidine (His) amino acid substitution and this polymorphism may lead to a lower enzyme activity and thermostability [11]. Epidemiological studies have shown inconsistent results for the association between the SULT1A1 G638A polymorphism and several malignancies including bladder cancer, lung cancer and breast cancer [12][13][14][15]. Moreover, due to its abundance in human tissues and significantly different expression among various genetic polymorphisms, SULT1A1 is considered to be a potentially cancer-predisposing gene.…”
Section: Introductionmentioning
confidence: 99%
“…From the Medline search using the search terms described earlier, we identified 34 case -control studies for SULT1A1 Arg 213 His polymorphism (Seth et al, 2000;Steiner et al, 2000;Bamber et al, 2001;Zheng et al, 2001Zheng et al, , 2003Ozawa et al, 2002;Wang et al, 2002;Nowell et al, 2002aNowell et al, , 2004Tang et al, 2003;Wu et al, 2003;Chacko et al, 2004;Hung et al, 2004;Langsenlehner et al, 2004;Liang et al, 2004;Tiemersma et al, 2004;Tsukino et al, 2004;Boccia et al, 2005Boccia et al, , 2006 with different types of cancers including UADT TRC, which is biologically more plausible, the studies included in meta-analysis were categorised according to the site of primary cancer as UADT TRC, genitourinary, breast, colorectal and other cancer sites. All the studies were further analysed with respect to genotypes, source of controls, ethnicity and carcinogen exposure.…”
Section: Resultsmentioning
confidence: 99%